Sound transmission across a finite simply supported double-laminated composite plate with enclosed air cavity - Thanh, Pham Ngoc; Thinh, Tran Ich (Vietnam Journal of Science and Technology, 2019)
ABSTRACTSound transmission across a finite orthotropic laminated double-composite plate with enclosed air cavity on an infinite acoustic rigid baffle is investigated analytically. Sound velocity potential method combined with simply supported boundary conditions is used instead of traditional methods, has good scalability and is important for studies of acoustic vibration of structures. The sound transmission loss is calculated from the ratio of incident to transmitted acoustic powers. Specifically, the focus is placed on the effects of several key system parameters on sound transmission including the plate dimensions, the laminate configurations, the boundary conditions, and the composite materials are systematically examined.